Host specificity in the Giardia duodenalis species complex - Cacciò, Simone M.; Lalle, Marco; Svärd, Staffan G. (Infection, genetics and evolution, 2018)
Giardia duodenalis is a unicellular flagellated parasite that infects the gastrointestinal tract of a wide range of mammalian species, including humans. Investigations of protein and DNA polymorphisms revealed that G. duodenalis should be considered as a species complex, whose members, despite being morphologically indistinguishable, can be classified into eight groups, or Assemblages, separated by large genetic distances. Assemblages display various degree of host specificity, with Assemblages A and B occurring in humans and many other hosts, Assemblage C and D in canids, Assemblage E in hoofed animals, Assemblage F in cats, Assemblage G in rodents, and Assemblage H in pinnipeds. The factors determining host specificity are only partially understood, and clearly involve both the host and the parasite. Here, we review the results of in vitro and in vivo experiments, and clinical observations to highlight relevant biological and genetic differences between Assemblages, with a focus on human infection. [Display omitted] •Giardia duodenalis Assemblages have different biologic and phenotypic characteristics.•Factors and mechanisms influencing clinical giardiasis are only partially understood.•Advanced in vitro models are needed to foster host-parasite interaction studies.•Integrated “omics” is needed to correlate genotype, phenotype and clinical outcome.